SYNTHESIS AND CHARACTERIZATION OF SALICYLALDEHYDE AND 2,4-DINITROPHENYL HYDRAZINE SCHIFF BASE WITH ITS COBALT (II) AND MANGANESE (II) COMPLEXES - Muhammad, Sani; Darma, Muhammad Suleiman; Bashir, Al-Amin (FUDMA JOURNAL OF SCIENCES, 2024)
The synthesis of Schiff base derived from salicylaldehyde and 2,4-dinitrophenyl hydrazine and its metal complexes were undertaken. This synthesis was achieved via the reflux condensation of salicylaldehyde and 2,4-dinitrophenyl hydrazine. Two metal complexes were prepared by coordinating the as-synthesized ligand with Cobalt (II) and Manganese (II) ions. The structures of the prepared ligand and the complexes were confirmed from the Fourier transformed infrared analysis. A laboratory tests were employed to study the melting and decomposition temperatures, Solubility, conductivity and magnetic susceptibility. The ligand obtained was a pale orange in colour with a percentage yield of 67% and melting point of 220ºC, The Cobalt(II) complex was found to be Orange in colour with 89% percentage yield and 250ºC decomposition temperature and the Manganese(II) complex was found to be a deep orange colour with 81% percentage yield and 246ºC decomposition temperature, The ligand and the complexes were found to be insoluble in water and slightly soluble in some common organic solvents, All the complexes are found to be paramagnetic in nature.